Autonomous visual exploration creates developmental change in familiarity and novelty seeking behaviors - Perone, Sammy; Spencer, John P. (Frontiers in Psychology, 2013)
What motivates children to radically transform themselves during early development? We addressed this question in the domain of infant visual exploration. Over the first year, infants’ exploration shifts from familiarity to novelty seeking. This shift is delayed in preterm relative to term infants and is stable within individuals over the course of the first year. Laboratory tasks have shed light on the nature of this familiarity-to-novelty shift, but it is not clear what motivates the infant to change her exploratory style. We probed this by letting a Dynamic Neural Field (DNF) model of visual exploration develop itself via accumulating experience in a virtual world. We then situated it in a canonical laboratory task. Much like infants, the model exhibited a familiarity-to-novelty shift. When we manipulated the initial conditions of the model, the model’s performance was developmentally delayed much like preterm infants. This delay was overcome by enhancing the model’s experience during development. We also found that the model’s performance was stable at the level of the individual. Our simulations indicate that novelty seeking emerges with no explicit motivational source via the accumulation of visual experience within a complex, dynamical exploratory system.